Evolution and adaptation of cultural architecture: survival strategies of the oil painting industry cluster in Songzhuang Art District, Beijing, China, under multiple pressures - Chen, Zhao; Mohd Ali, Noor Azizi; Hasna, Mohd Fabian (AccScience Publishing, 2025)
Since the late 20th century, art districts have emerged as increasingly important cultural spaces within the social fabric. However, the growing influence of capital, urban development pressures, and constraints on artistic expression has transformed some art districts into commercialized zones with diminished industrial depth. This study focuses on the adaptive mechanisms employed by the oil painting industry cluster in Beijing’s Songzhuang art district in response to a range of multidimensional challenges. A comprehensive methodology comprising semi-structured interviews, participatory observation, and literature analysis was adopted to construct a systematic framework for survival strategies. The findings indicate that the cluster’s sustainable development hinges on three key factors: artistic innovation capability, economic synergy, and social inclusivity. Based on this analysis, the study suggests enhancing cluster resilience while preserving its cultural characteristics through three aspects: optimizing spatial resources, supporting creative systems, and fostering community engagement.